ARSITEKTUR JAMINAN KESEHATAN INDONESIA: CAPAIAN, KRITIK DAN TANTANGAN MASA DEPAN (THE ARCHITECTURE OF INDONESIAN HEALTH INSURANCE: ACHIEVEMENT, CRITIQUE, AND FUTURE CHALLENGE) - Silvester Hari Purnomo (Berkala Ilmiah Kedokteran Duta Wacana, 2020)
This book has thoroughly described the achievements, critiques, and challenges in the future of the Indonesian health insurance architecture. The author describes his vision of the ideal universal health coverage (UHC) for the country impeccably. His experience as a general practitioner and public health practitioner since the early days of national insurance establishment has shaped his writing style. The author opens with an introduction to the principles of health insurance, such as the aggregation of funds and insurance risks. He also describes the health insurance scheme in various countries before discussing Indonesia’s situation. The historical development of Indonesian health insurance is aptly presented. Its concepts, albeit under frequent changes are presented as though they have already manifested in architecture. Detailed programmes of the national health insurance, which is organised by BPJS Kesehatan (Badan Penyelenggara Jaminan Sosial Kesehatan) are presented with its challenges and difficulties. The frequent adjustment of fund collection and service payment scheme (e.g. the utilisation of case-based group method to replace the diagnosis-related group in service payment scheme) is also described thoroughly. Outstanding claim with a lag of payment time to the service providers is another example of the system shortcoming mentioned in this book. The author emphasises on the breadth of primary care coverage which includes government-owned primary health care centred and private general practitioners’ clinics. Regardless of the valuable information on the national insurance scheme, there is a lack of the definition and the systematic description of the “architecture” terminology. The readers might need a further picture of the dynamics of a new-born UHC system. The book seems to be directed to the general readers, yet placing more sophisticated knowledge which suitable for higher education students from health or medical discipline. This warrants further clarification on the scope of the audience and reorganises the contents accordingly. There is a potential for utilisation for educational purposes, where the chapter organisation may be modified to the number of periodic class sessions, including a chapter dedicated to changing issues and future challenges. The author has incorporated actual data, visualised in various graphs. However, the print quality is lacking so the readers might difficult to interpret them. The general population needs enticing figures, while the academic audience would prefer detailed graphics and data tabulation. In addition, there are important changes in the insurance policy between print date and this review, such as the significant change in insurance premium. This issue is quite important to be added in the future revisions. The reviewer deems the book important. The book itself has its own architecture, achievement, critiques, and challenges. Despite the effort to reach readers from the general population, the medical and health finance policy students would be the most benefited audience. This book is a good introduction to more advanced topics in the health insurance discipline, with routine revisions on dynamic changes in Indonesian healthcare insurance architecture.